Penerapan Metode Numbered Head Together dalam Materi Teori Relativitas Khusus pada Kelas XII MIPA 3 di SMAN 1 Jember - Bekti Haryo Putri, Novita; Ainur Rohmah, Siti; Sholihah, Lailatus (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2023)
Increasingly advanced technology requires teachers to continue to update and use technology as well as possible in the learning process. Physics learning which is synonymous with theory and concepts and has an abstract impression on class XII material is an opportunity for teachers to utilize technology in making worksheets by applying the numbered head together (NHT) learning method in practice. This research is a classroom action research conducted in two cycles in class XII MIPA 3 SMAN 1 Jember with data collection techniques using pre-test and post-test. Applying the NHT method means providing opportunities for all students in the class to exchange opinions and have the courage to express their opinions in groups and in front of the class which will motivate students' learning as well. Through the application of the NHT method, students' cognitive learning outcomes (n-gain) were obtained in cycle I of 0.17 in the low category (not yet significant) and in cycle II of 0.61 in the moderate category (significant enough). Based on these results, it can be concluded that there is an increase in n-gain acquisition which indicates an increase in cognitive learning outcomes of students in class XII MIPA 3 SMAN 1 Jember